An elephant in the room - Devji, F (Duke University Press, 2019)
Torn between a futurist vision of Pakistan, on one hand, and the desire for a conventionally historical narrative about its founding on the other, Muslim nationalism has always faced its past in the form of impossibility. As Devji discusses in this afterword, the essays in the special section “The Past for Pakistan” explore Pakistan's tormented relationship with history each in its own way, and whether this past is given the name of India or Islam. If Salma Siddique writes about the undecidability of origins in cinematic culture, Shruti Kapila demonstrates how Pakistan was imagined outside its own ideology and categories. Where Nayanika Mookherjee explores the different forms of historical amnesia and memory that define nationality in both wings of what was once Pakistan, Chris Moffat writes about the commemoration of transient and non-national pasts in the country's present.